The Development of an Interactive Busy Book as a Learning Medium for Introducing Sex Education in Early Childhood - Tang, Bunga; Sabani, Fatmaridah; Saputri Laswi, Aishiyah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to develop an interactive Busy Book as a learning medium for introducing sex education to children aged 5ÔÇô6 years. The development process followed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data collection involved interviews, documentation, and questionnaires with content experts, media experts, and B-class teachers. The validation results showed scores of 74% from the content expert and 84.4% from the media expert, while the practicality test yielded a score of 96.3%. The developed Busy Book was found to be suitable for use in teaching and is relevant as a tool for introducing basic sex education concepts appropriate for early childhood development.┬á┬á